Seasonal urbanism: landscape architecture for winter-active public spaces - Stokmane, Ilze; Vasiļjeva, Agnese (Landscape Architecture and Art, 2025)
The research explores the contemporary topic of landscape seasonality, with a particular focus on the winter period, which is often an ‘afterthought’ in landscape planning. The issues affecting the urban environment of many municipalities during the winter season are brought into focus by changing weather conditions, when roads become impassable, car parks inaccessible and pavements impassable. The collection or beneficial use of snow on site poses new challenges for urban planning, as creating a safe environment is an essential aspect of the speciality of landscape architecture, reducing any health risks for citizens in every possible way. In order to be able to adapt the infrastructure of public outdoor spaces to seasonal use, it is necessary to define qualitative seasonal urban planning approaches by looking at the existing problems, therefore it was developed criteria for the evaluation and analyses of specific landscape spaces. The study examines the experience of several municipalities in seasonal landscape planning, conducting a survey of citizens and interviews with experts in the field, thus looking in depth for solutions to these problems in Latvia. The study has led to the development of illustrative detailed urban examples for the seasonal landscaping and use of different public outdoor spaces.